1990
DOI: 10.1088/0953-8984/2/44/013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the image potential on the binding energy of hydrogenic impurities in semiconductor quantum wells

Abstract: The authors report the results of a variational calculation of the binding energy of shallow donors in quantum wells along with the effects of the image potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In conclusion we note, that the image potential effects on the excitonic properties are weak for systems with small dserencies of the background dielectric constant, especially for the system GaAs-Ga,-,AI,As. This is in agreement with recent calculations of the hydrogenic donor binding energy (Wendler and Hartwig 1990). But our calculations show, that it is necessary to include both image parts, the mutual and the self-image parts.…”
Section: (8)supporting
confidence: 93%
“…In conclusion we note, that the image potential effects on the excitonic properties are weak for systems with small dserencies of the background dielectric constant, especially for the system GaAs-Ga,-,AI,As. This is in agreement with recent calculations of the hydrogenic donor binding energy (Wendler and Hartwig 1990). But our calculations show, that it is necessary to include both image parts, the mutual and the self-image parts.…”
Section: (8)supporting
confidence: 93%
“…It is found that, for a quantum wire with dielectric discontinuity, the hole-acceptor attraction potential has a non-Coulombic form [22,26]. However, Wendler and Hartwig [27] studied the effect of the image potential on the binding energy of hydrogenic impurities in semiconductor quantum wells. They found that, when all image contributions (the mutual image potential between the hydrogenic impurity and the electron and the self-image potentials of the two particles) are taken into consideration, the image potential effects on the hydrogenic donor binding energy will be weak for donor positions in the centre of the quantum well.…”
Section: Introductionmentioning
confidence: 99%
“…13 but for the v-motion case and various electron kinetic energies E 0 at least checked. As an example, one can mention calculations of electronic levels in semiconductor quantum superlattices [80,82,87,99,100] or metal-insulator-semiconductor structures [79,95], as well as impurity energy levels [82,84]. Tunnel currents in layered structures [135][136][137][138] should be investigated (see also Refs.…”
Section: Discussionmentioning
confidence: 99%
“…In this case not only the plasmon excitations [33,69,70] but also polar phonons are involved [33,[36][37][38][39][40][41]. It should be stressed that even in the static limit the energy W does not diverge at the interface [15,17,60,[71][72][73][74][75], contrary to the still unequivocally used classical expressions which can be sometimes found in literature [69,[76][77][78][79][80][81][82][83][84][85][86][87].…”
Section: Introductionmentioning
confidence: 99%